Impact of COVID-19 – Experiences of 5th year medical students at the University of KwaZulu-Natal - Andrew J. Ross (South African Family Practice)
Background: The global pandemic associated with coronavirus disease 2019 (COVID-19) had a considerable effect on higher education in South Africa, with online instruction replacing traditional lectures for many students. Medical students were required to vacate their residences in March 2020 but returned to campus in July 2020 to enable them to continue with clinical teaching and learning. The aim of this study was to understand the learning experiences of 5th year medical students at the University of KwaZulu-Natal (UKZN) during 2020.